ANALISIS KUTUB PERTUMBUHAN DAN PENGARUH HUMAN CAPITAL TERHADAP PERTUMBUHAN EKONOMI REGIONAL DI PROVINSI LAMPUNG TAHUN 2002-2011 - , Iwan Meylani; , Prof. Mudrajad Kuncoro., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the growth poles and the impact of human capital on regional economic growth in Lampung Province during 2002-2011. Human capital is proxied by mean years of schooling and adult literacy rate. The data used are secondary data from Central Statistics Agency (BPS) and Regional Development Planning Board (Bappeda) of Lampung Province. This study was initiated by identifying regencies/cities which are growth poles of Lampung Province using the analysis of real Gross Regional Domestic Product (GRDP) per capita growth as Kubis, Titze, and Ragnitz (2007). Furthermore, the growth spillover effects were analyzed by using the Capelloâs formula (2009). To determine the variables that characterize the regencies/cities as growth poles and non-growth poles, used discriminant analysis with stepwise method. Finally, panel data regression analysis with fixed effect model to estimate the impact of human capital on economic growth in Lampung Province. This study found that Bandar Lampung is the growth pole in Lampung Province and there is no high inequality of growth spillover effects that received by the regencies and cities in Lampung Province. The number of workers and average years of schooling are dominant distinguishing characteristics of the classification of regencies and cities as growth poles and non-growth poles. Both average years of schooling and adult literacy rate, as human capital variables, have significantly positive impact on economic growth in Lampung Province during 2002-2011. It can be concluded that human capital is one of the main regional economic growth determinants in Lampung Province.